The development, manufacture and evaluation of a selfmicro-emulsifying drug delivery system for efavirenz - Musakana, Tanyaradzwa Gracious (Rhodes University, Faculty of Pharmacy, Pharmacy, 2018)
Expected release date-April 2020
Keywords: Uncatalogued